High throughput discovery of thermo‐responsive materials using water contact angle measurements and time‐of‐flight secondary ion mass spectrometry. (8th March 2012) - Hook, Andrew L.; Scurr, David J.; Anderson, Daniel G.; Langer, Robert; Williams, Paul; Davies, Martyn; Alexander, Morgan
<x xml:space="preserve">Abstract</x> Switchable materials that alter their chemical or physical properties in response to external stimuli allow for temporal control of material‐biological interactions, thus, are of interest for many biomaterial applications. Our interest is the discovery of new materials suitable to the specific requirements of certain biological systems. A high throughput methodology has been developed to screen a library of polymers for thermo‐responsiveness, which has resulted in the identification of novel switchable materials. To elucidate the mechanism by which the materials switch, time‐of‐flight secondary ion mass spectrometry has been employed to analyse the top 2 nm of the polymer samples at different temperatures. The surface enrichment of certain molecular fragments has been identified by time‐of‐flight secondary ion mass spectrometry analysis at different temperatures, suggesting an altered molecular conformation. In one example, a switch between an extended and collapsed conformation is inferred. Copyright © 2012 John Wiley & Sons, Ltd.